2013
DOI: 10.4236/sgre.2013.43034
|View full text |Cite
|
Sign up to set email alerts
|

Waste Frying Oils-Based Biodiesel: Process and Fuel Properties

Abstract: The conversion of waste frying oil into a valuable methyl ester (biodiesel) has been successfully conducted and also the acid pre-treatment process was carried out prior to the main biodiesel production process for lowering waste frying oil free fatty acid (FFA) content below 1%. The physicochemical properties of biodiesel were analyzed to ensure the product could meet the standards of fuel properties. The methanolysis was selected as the biodiesel production technique under various mixing speeds namely 350, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It has been estimated that biodiesel, and more specifically bio-ethanol, could supplant roughly 10% of the diesel fuel consumed within European continent total fuel demand [1]- [3]. The alternative fuel that will replace part or all of the petroleum diesel fuel must be in fact attainable, economically competitive, ecologically satisfactory, and promptly accessible [1], [4], [5]. A considerable lot of these essentials are met by vegetable oils, or by and large, by triglycerides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that biodiesel, and more specifically bio-ethanol, could supplant roughly 10% of the diesel fuel consumed within European continent total fuel demand [1]- [3]. The alternative fuel that will replace part or all of the petroleum diesel fuel must be in fact attainable, economically competitive, ecologically satisfactory, and promptly accessible [1], [4], [5]. A considerable lot of these essentials are met by vegetable oils, or by and large, by triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial amounts of utilized frying oil are accessible all through the world. In Jordan the amount of UFO range 320 million liters/year and in the US alone the amount of UFO ranges from 5 billion to 12 billion liters a year [2]- [4]. in some places, frying oil used in the manufacturing of soap also as an additive for fodder preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The entire physical and chemical properties (such as: density, kinematic viscosity, flash point, saponification number, acid value, iodine value, calorific value, moisture content, and pour point) analysis were carried out using ASTM D6751 [7].…”
Section: Methodsmentioning
confidence: 99%
“…The transformation of crop triglycerides into methyl ester (ME) occurs in the presence of a catalyst. The catalyst can be an alkali, acid or enzyme, and its type depends on the properties of feedstock and conditions of the reaction [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…If the process used alkaline catalyst, the process needs reaction time of 2-4 hours for complete reaction to biodiesel production. Several researchers was reported that the better results and industrial scale, the alkaline catalyst is the most commonly used due to low cost, easy to install and shorter reaction time [14][15]. In recent years, ultrasound a useful tool for strengthening the mass transfer of the liquid-liquid systems, has gained much more interest of many researchers [13].…”
Section: Introductionmentioning
confidence: 99%